2017
DOI: 10.1002/bit.26434
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli “TatExpress” strains super‐secrete human growth hormone into the bacterial periplasm by the Tat pathway

Abstract: Numerous high‐value proteins are secreted into the Escherichia coli periplasm by the General Secretory (Sec) pathway, but Sec‐based production chassis cannot handle many potential target proteins. The Tat pathway offers a promising alternative because it transports fully folded proteins; however, yields have been too low for commercial use. To facilitate Tat export, we have engineered the TatExpress series of super‐secreting strains by introducing the strong inducible bacterial promoter, ptac, upstream of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 24 publications
1
52
0
Order By: Relevance
“…In this pathway, the protein cargo must be either completely or partially unfolded to be secreted. In the case of secretion of peptides or smaller proteins, studies have reported extremely high production (Browning et al, 2017;Chen et al, 2014), for example, 6 g/L of 13.1-kDa Fab (Voulgaris, Finka, Uden, & Hoare, 2015). Small proteins or peptides are secreted into the periplasm by the Type II secretion system with extracellular secretion using a leaky outer membrane.…”
Section: Possibility Of Omvs As a Tool For Protein Secretionmentioning
confidence: 99%
“…In this pathway, the protein cargo must be either completely or partially unfolded to be secreted. In the case of secretion of peptides or smaller proteins, studies have reported extremely high production (Browning et al, 2017;Chen et al, 2014), for example, 6 g/L of 13.1-kDa Fab (Voulgaris, Finka, Uden, & Hoare, 2015). Small proteins or peptides are secreted into the periplasm by the Type II secretion system with extracellular secretion using a leaky outer membrane.…”
Section: Possibility Of Omvs As a Tool For Protein Secretionmentioning
confidence: 99%
“…The twin-arginine translocase offers the potential for the biotechnology industry owing to its ability to transport fully-folded proteins into the periplasm of E. coli. Initial studies confirmed the capability of the Tat system to transport a model heterologous protein to a high yield (Matos et al, 2012), and more recent data has shown that substrates are not limited to GFP with Tat being able to transport hGH, scFv, and interferon α2b (Alanen et al, 2015;Browning et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…Initial studies confirmed the capability of the Tat system to transport a model heterologous protein to a high yield (Matos et al, 2012), and more recent data has shown that substrates are not limited to GFP with Tat being able to transport hGH, scFv, and interferon α2b (Alanen et al, 2015;Browning et al, 2017). Initial studies confirmed the capability of the Tat system to transport a model heterologous protein to a high yield (Matos et al, 2012), and more recent data has shown that substrates are not limited to GFP with Tat being able to transport hGH, scFv, and interferon α2b (Alanen et al, 2015;Browning et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…No negative impact on cell growth or target integrity was detected [94], but the translocation is limited by the PMF, which is the main energy source of the translocon. [95] An additional coexpression of phage-shock protein A (PspA), which maintains the PMF, can further increase the translocation efficiency [96]. Placing ptac upstream of the chromosomal tatABCD operon has also been shown to facilitate Tat export.…”
Section: Tat-pathwaymentioning
confidence: 99%